2021
DOI: 10.2147/rru.s299358
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Trial to Evaluate the Effectiveness of Watching Movies to Decrease Anxiety During Extracorporeal Shock Wave Lithotripsy

Abstract: Background Extracorporeal shock wave lithotripsy (ESWL) is the only non-invasive treatment for urolithiasis; however, it can cause anxiety and pain for patients. Several new nonpharmacological adjuvant approaches have been developed to reduce adverse events. Objective To analyze the efficacy of watching movies during ESWL to relieve anxiety and pain. Methods A total of 84 patients were randomly divided into two groups. The experimental group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Historically, motion pictures have shown great therapeutic value in the form of cinematherapy 18 , most commonly in psychotherapy [19][20][21] , general psychological interventions 22 , or treating schizophrenia 23,24 . Research has shown that using films as a therapeutic adjunct can have beneficial effects even in somatic fields such as nephology 25 and urology 26 . The most commonly known educational value in motion pictures comes from educational films (or public health films) and patient videos, whose history [27][28][29][30][31] and therapeutic benefits 32,33 have been well researched.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, motion pictures have shown great therapeutic value in the form of cinematherapy 18 , most commonly in psychotherapy [19][20][21] , general psychological interventions 22 , or treating schizophrenia 23,24 . Research has shown that using films as a therapeutic adjunct can have beneficial effects even in somatic fields such as nephology 25 and urology 26 . The most commonly known educational value in motion pictures comes from educational films (or public health films) and patient videos, whose history [27][28][29][30][31] and therapeutic benefits 32,33 have been well researched.…”
Section: Resultsmentioning
confidence: 99%
“…***These 2 studies did not provide additional data on the relationship between psychological distress and urolithiasis but included data on rates of psychological distress and as such were included in this review. measures of state 43,[60][61][62][63][64][65] and trait 66 anxiety, or on a visual analogue scale anxiety measure 67 compared to urolithiasis controls who did not receive these additional interventions. 43,[60][61][62][63][64][65][66][67] Similarly, urolithiasis patients had lower scores on a simple visual analogue scale anxiety measure (lower anxiety) following transcutaneous electrical nerve stimulation intervention in emergency care 68 or auricular acupressure intervention before SWL, 69 compared to urolithiasis patients who did not receive these interventions.…”
Section: Psychological Distress and Urological Treatmentmentioning
confidence: 99%
“…measures of state 43,[60][61][62][63][64][65] and trait 66 anxiety, or on a visual analogue scale anxiety measure 67 compared to urolithiasis controls who did not receive these additional interventions. 43,[60][61][62][63][64][65][66][67] Similarly, urolithiasis patients had lower scores on a simple visual analogue scale anxiety measure (lower anxiety) following transcutaneous electrical nerve stimulation intervention in emergency care 68 or auricular acupressure intervention before SWL, 69 compared to urolithiasis patients who did not receive these interventions. In addition, patients who underwent nursing care interventions [70][71][72] or a real-time video during flexible URS intervention 73 had lower anxiety, [70][71][72][73] as well as depression, [70][71][72][73] and higher MH 70 mean scores in the intervention group compared to patients who did not receive intervention.…”
Section: Psychological Distress and Urological Treatmentmentioning
confidence: 99%
“…To date, treatment strategies in the management of urolithiasis are mainly based on minimally invasive procedures, with a preference for endourologic techniques, which include extracorporeal shock wave lithotripsy, retrograde intrarenal surgery, and percutaneous nephrolithotomy (PCNL). 1 , 2 PCNL is the procedure of choice for eliminating large (>2 cm) and complex renal stones, but achieving complete stone clearance in a single approach may require using multiple access tracts. 3 , 4 The large number of tracts and the need for renal parenchymal manipulation leads to more kidney parenchymal injuries, requires PRC transfusion, and sometime contributes to various serious complications, such as uncontrolled hemorrhage and massive hemothorax.…”
Section: Introductionmentioning
confidence: 99%